2004
DOI: 10.1002/chin.200434072
|View full text |Cite
|
Sign up to set email alerts
|

Triphenylphosphine Catalyzed Stereoselective Synthesis of O‐Vinylcyclopentenones.

Abstract: Triphenylphosphine Catalyzed Stereoselective Synthesis of O-Vinylcyclopentenones. -The procedure described represents a simple entry into the synthesis of O-vinylcyclopentenones (III) thought as potentially synthetic intermediates. -(BAHARFAR*, R.; OSTADZADEH, A.; ABBASI, A.; J. Chem. Res., Synop. 2004, 1, 37-38; Dep. Chem., Mazandaran Univ., Babolsar 47415, Iran; Eng.) -H. Haber 34-072

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The recent work of Robabeh Baharfar,9 showed that the Zwitterionic intermediates formed between alkyl isocyanides (1) and dialkyl acetylenedicarboxylates (2) react with 1,3-diimino isoindoline (3) to afford functionalized 2,6-dihydro[2,1-a]isoindole derivatives (4) and ( 5) in good yields along with N-vinyl isoindoles (6) as by-product (Scheme 1).…”
mentioning
confidence: 99%
“…The recent work of Robabeh Baharfar,9 showed that the Zwitterionic intermediates formed between alkyl isocyanides (1) and dialkyl acetylenedicarboxylates (2) react with 1,3-diimino isoindoline (3) to afford functionalized 2,6-dihydro[2,1-a]isoindole derivatives (4) and ( 5) in good yields along with N-vinyl isoindoles (6) as by-product (Scheme 1).…”
mentioning
confidence: 99%